Differences in parental perceptions of walking and cycling to high school according to distance. (May 2020) - Mandic, Sandra; Hopkins, Debbie; García Bengoechea, Enrique; Flaherty, Charlotte; Coppell, Kirsten; Moore, Antoni; Williams, John; Spence, John C.
Graphical abstract: Highlights: Parents of adolescents favoured walking compared to cycling to school. Parental perceptions of active modes differed based on distance to school. With increasing distance to school, social support for active transport decreased. Personal, environmental and safety barriers became more pronounced with distance. Two-thirds of parents expected to participate in adolescents' school travel decision-making. Abstract: Background: Parental perceptions towards different modes of transport correlate with adolescents' mode choice for school trips. Whether parental attitudes differ for walking versus cycling and/or home-to-school distance is unknown. We compared parental perceptions of walking versus cycling to school in adolescents in Dunedin, New Zealand and examined whether mode-specific barriers differ by distance to school. Methods: Parents (n = 341; age: 47.5 ± 5.2 years; 77.1% females) completed a survey about their adolescent's (age: 13–18 years; 48.1% boys) school travel and their own perceptions of walking/cycling to school. Participants were categorised into three groups according to distance to school as 'walkable' (≤2.25 km), 'cyclable' (>2.25–≤4.0 km) and 'beyond cyclable' (>4.0 km). Results: Common modes of transport to school differed significantly across the 'walkable'/'cyclable'/'beyond cyclable' categories (car passenger: 25.7%/40.5%/60.6%; public/school bus: 5.5%/15.4%/28.4%; walking: 66.2%/28.2%/1.2%; cycling: 0.0%/7.7%/0.5%; all p < 0.001). Compared to walking, parents perceived cycling to school to be less important (walking/cycling: 87.5%/62.5%), with less social support from parents (46.2%/17.1%), peers (20.6%/4.8%) and school (24.5%/12.4%), less interest from adolescents (48.5%/31.9%), fewer cycle paths (26.5%) versus footpaths (65.0%) and more safety concerns (35.0%/64.6%; all p < 0.001). As distance to school increased, parents' social support decreased whereas personal, environmental and safety-related barriers increased for both modes, with less consistent findings for cycling. Overall, 68.2% of parents expected to participate in adolescents' walking/cycling to school decision-making. Conclusions: Parents favoured walking compared to cycling to school with parental attitudes for both modes changing with increasing distance to school. The findings illustrate the importance of addressing parental concerns, considering the specificity of walking and cycling and taking into account distance to school in active transport to school initiatives.